Respuesta :

Answer:

Answer is in explanation.

Step-by-step explanation:

Part A:

The [tex]x[/tex]-coordinate of the intersection of the curves for the equations [tex]y=4^{-x}[/tex] and [tex]y=2^{x+3}[/tex] is the same as the solution to [tex]4^{-x}=2^{x+3}[/tex] because the equation [tex]4^{-x}=2^{x+3}[/tex] is the result of finding when (for what [tex]x[/tex]'s) the [tex]y[/tex]'s are the same for the the equations [tex]y=4^{-x}[/tex] and [tex]y=2^{x+3}[/tex].

Part B:

Table for [tex]y=4^{-x}[/tex]:

[tex]x[/tex]  |          [tex]y=4^{-x}[/tex]                     |  [tex](x,y=4^{-x})[/tex] |

-3                |          [tex]y=4^{-(-3)}=4^{3}=64[/tex] | [tex](-3,64)[/tex] |

-2                |          [tex]y=4^{-(-2)}=4^{2}=16[/tex]  | [tex](-2,16)[/tex] |

-1                 |          [tex]y=4^{-(-1)}=4^{1}=4[/tex]     | [tex](-1,4)[/tex]

0                 |          [tex]y=4^{-(0)}=4^{0}=1[/tex]     | [tex](0,1)[/tex]

1                  |          [tex]y=4^{-(1)}=4^{-1}=\frac{1}{4}[/tex] | [tex](1,\frac{1}{4})[/tex]

2                 |          [tex]y=4^{-(2)}=4^{-2}=\frac{1}{16}[/tex] | [tex](2,\frac{1}{16})[/tex]

3                 |          [tex]y=4^{-(3)}=4^{-3}=\frac{1}{64}[/tex] | [tex](3,\frac{1}{64})[/tex]

Table for [tex]y=2^{x+3}[/tex]:

[tex]x[/tex]  |        [tex]y=2^{x+3}[/tex]                   | [tex](x,y=2^{x+3})[/tex] |

-3                |        [tex]y=2^{-3+3}=2^{0}=1[/tex]    | [tex](-3,1)[/tex]

-2                |        [tex]y=2^{-2+3}=2^{1}=2[/tex]    | [tex](-2,2)[/tex]

-1                |        [tex]y=2^{-1+3}=2^{2}=4[/tex]    | [tex](-1,4)[/tex]

0                |        [tex]y=2^{0+3}=2^{3}=8[/tex]    | [tex](0,8)[/tex]

1                |        [tex]y=2^{1+3}=2^{4}=16[/tex]    | [tex](1,16)[/tex]

2                |        [tex]y=2^{2+3}=2^{5}=32[/tex]    | [tex](2,32)[/tex]

3               |        [tex]y=2^{3+3}=2^{6}=64[/tex]    | [tex](3,64)[/tex]

You can see in the two tables the y-coordinates are the same value of [tex]4[/tex] when [tex]x=-1[/tex]. So basically the common point in both tables is [tex](-1,4)[/tex] so [tex](-1,4)[/tex] is a solution.

Part C:

I'm going to graph both [tex]y=4^{-x}[/tex] and [tex]y=2^{x+3}[/tex] on the same coordinate plane. I will then find where they will intersect.

I'm going to graph my points from the table to [tex]y=4^{-x}[/tex] and [tex]y=2^{x+3}[/tex].

This can be seen in my drawing.

I graphed [tex]y=4^{-x}[/tex] in blue.

I graphed [tex]y=2^{x+3}[/tex] in red.

Another way:

An algebraic approach:

[tex]4^{-x}=2^{x+3}[/tex]

[tex](2^2)^{-x}=2^{x+3}[/tex] (since [tex]4=2^2[/tex] and now the bases on both side are the same)

[tex]2^{-2x}=2^{x+3}[/tex]

[tex]-2x=x+3[/tex] (since [tex]2^{a}=2^{b}[/tex] then [tex]a=b[/tex])

[tex]-3x=3[/tex] (subtracted [tex]x[/tex] on both sides)

[tex]x=-1[/tex] (divided both sides by [tex]-3[/tex])

The solution is [tex]x=-1[/tex].

Ver imagen freckledspots
ACCESS MORE